Does My Head Look Big in This? - Randa Abdel-Fattah (London, United Kingdom Scholastic, 2006)
Don't panic - I'm Islamic| Amal is a 16-year-old Melbourne teen with all the usual obsessions about boys, chocolate and Cosmo magazine. She's also a Muslim, struggling to honour the Islamic faith in a society that doesn't understand it. The story of her decision to "shawl up" and its attendent anxieties (like how much eyeliner to wear) is funny, surprising and touching by turns.
Keywords: Realistic Fiction -- Realistic Fiction